Da'wah in contemporary Japanese society: a case study of Tokyo mosque - Siddiqi, Muhammad Abdur Rahman; Ali, Muhammad Mumtaz (IIUM Press, International Islamic University Malaysia, 2017)
This is a case study on Tokyo Mosque and the da'wah activities in Japan among contemporary Japanese and local Muslims. It deals with the arrival of Muslims in Japan and the establishment of Islamic da'wah organizations and mosques. It studies the Muslim perception and sensitivities in the context of the current da'wah situation in the Japanese society and relations with various religions and culture of Japan. The main aim of this research is to explore and analyse the origin of the organised da'wah activities at Tokyo Mosque and its impact. This study also traces the inner problematic issues related to daÑwah and its challenges for the realization of peaceful coexistence among the Muslims and Japanese in Japan. The book specially focuses on the debate and dialogue of the Muslims with the followers of other religions and cultures in Japan as this will decide the future attitude of IslÉm and Muslims in Japan and its relation to the Japanese community. It attempts to assess the structure, organization and the pivotal role of Tokyo Mosque and its educational activities. It explores the position of IslÉm and Muslims and their interaction with a completely different culture of Emperor worship of the past and a highly modernized, industrial and civilized nation. This includes the study of the strategy Muslims have adopted for daÑwah and their fresh understanding and analysis with reference to Tokyo Mosque